Research on the Interaction between Epigallocatechin Gallate and Millet Bran Protein - MIAO Xiang-shuo; CHANG Cheng-ming; HE Dong-qin (Liang you shipin ke-ji, 2022)
Interaction between epigallocatechin gallate (EGCG) and millet bran protein under conditions that simulate human physiological conditions was investigated by Endogenous fluorescence spectroscopy synchronous fluorescence spectroscopy, Three-dimensional fluorescence spectroscopy and ultraviolet-visible spectroscopy. The results indicated that EGCG can greatly quench the endogenous fluorescence of millet bran protein in the mixed of static mode and dynamic mode. Synchronous fluorescence spectroscopy, ultraviolet-visible spectroscopy and three-dimensional fluorescence spectroscopy indicated that EGCG changed the protein peptide backbone and microenvironment of aromatic amino acid residues of millet bran protein. The synchronous fluorescence results showed that they mainly affected the microenvironment around tryptophan residues and reduced the hydrophobicity of the surrounding microenvironment. The binding constants (KA) and site numbers (n) between EGCG and millet bran protein obtained at different temperatures were 8.691 6×104 L/moL, 1.084 8 (290 K); 1.317 0×106 L/moL, 1.300 9 (298 K); 7.868 6×106 L/moL, 1.489 3 (310 K), respectively. According to the thermodynamic parameters, EGCG and millet bran protein were combined by hydrophobic interaction to form a complex. The binding distance (r) between EGCG and millet bran protein was calculated to be about 2.341 8 nm based on the theory of Föster’s non-radiation energy transfer. The theoretical model of the binding ratio between EGCG and millet bran protein at different temperatures was established, and the binding ratio between EGCG and millet bran protein decreased as concentration of EGCG increased, while the temperature had effect on the binding ratio.